Corba-based multi-agent systems environment - Li, Yong (2008)
This dissertation will give a detailed analysis on the current status of research on multi-agent systems environment, and engage in building a CORBA-based prototype system to demonstrate the functionality of a multi-agent systems execution environment, which supports FIPA-Agent Communication Language among others.